Exploration des syles de résolution de conflits chez les jeunes du secondaire ayant des troubles de comportement. - Dolgos, Sandra. (University of Ottawa (Canada), 1998)
Eighty-seven high school students completed a modified version of the Organizational Communication Conflict Instrument: 38 students had behavioral problems and 49 didn't. Result indicate that all these students use significantly more control strategies than solution-orientation or non-confrontation strategies to resolve conflicts with their peers. T-tests identified several significant differences ($\alpha$ = 0.05): (1) boys with behavioral problems use significantly less non-confrontation strategies than boys without behavioral problems; (2) girls with behavioral problems use significantly less solution-orientation strategies than girls without behavioral problems; (3) boys with behavioral problems use significantly more solution-orientation strategies than girls with behavioral problems. Furthermore, although only significant at $\alpha$ = 0.07, boys with behavioral problems belonging to non-nuclear families use control strategies more than boys from nuclear families. These findings show however that all high school students could benefit from conflict resolution programs.
Keywords: Education, Special.